Patients with systemic diseases treated with dental implants - Koszuta, Agnieszka; Szymańska, Jolanta; Kubić-Filiks, Beata (Polish Journal of Public Health, 2013)
Introduction. The success of implant prosthetic treatment of missing teeth consists in the full integration of the implant with the bone and proper functioning of denture based on it. This is significantly influenced by systemic factors.Aim. The aim of this study was to evaluate the prevalence of systemic diseases among the patients treated with dental implants.Material and methods. The survey was conducted among 464 patients of both sexes aged from 20 to 74 years, treated with dental implants at the Non-Public Healthcare Centre “Dental” in Tomaszów Mazowiecki. The patients answered an anonymous questionnaire. Questions concerned age, place of residence and systemic diseases.Results. The results of the survey indicate that nearly 40% of all patients treated with dental implants were people suffering from systemic diseases, significantly more often they were persons aged 40-60 years.Conclusions. Persons living in rural areas or small town suffering from systemic diseases often decided to have implants. In addition, the residents of the city made that decision often when they did not suffer from systemic diseases